Improving larval performance of Macrobrachium rosenbergii (De Man 1879) through treating broodstock with phloroglucinol : - Ngatunga, Bernard Benjamin (Trường Đại học Cần Thơ, 2019)
The overall objective of this study was to examine the possibility of using phloroglucinol treating (conditioning) on giant freshwater prawn M. rosenbergii broodstock to improve larval performance.